2004
DOI: 10.1111/j.1745-4514.2004.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Glucose 6-Phosphate Dehydrogenase From Coriander (Coriandrum Sativum) Leaves

Abstract: Glucose‐6‐phosphate dehydrogenase (D‐glucose‐6‐phosphate: NADP+ oxidoreductase, EC 1.1.1.49; G6PD) was purified from coriander (Coriandrum sativum) leaves; the kinetic behavior and some properties of the enzyme were also investigated. The purification was done at 4C and involved two steps: ammonium sulfate fractionation, and DEAE‐Sephadex A50 ion exchange chromatography. The enzyme was obtained with a yield of 26.4% and had a specific activity of 1.826 U/mg protein. Optimum pH, stable pH, optimum temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 28 publications
0
15
2
Order By: Relevance
“…The subunit molecular weight of pigeon pea glucose-6-phosphate dehydrogenase was found to be quite close to the molecular weight of enzyme obtained from Cryptococcus neoformans (50 KDa) [32], A. vinelandii (52 KDa) [33], dog liver (52.5 KDa) [34], A. aculeatus (52 ± 1.1 KDa) [15], goat erythrocyte (52 KDa) [35]. However, the value is lower than as reported from Pseudomonas W6 [29], pig liver [20], turkey erythrocyte [36], coriander [24] and rainbow trout [37]. The result revealed that pigeon pea glucose-6-phosphate dehydrogenase is a homodimer with molecular weight of 113 KDa and subunit molecular weight approximately equals to 55 KDa.…”
Section: Molecular Weight Determinationcontrasting
confidence: 47%
See 4 more Smart Citations
“…The subunit molecular weight of pigeon pea glucose-6-phosphate dehydrogenase was found to be quite close to the molecular weight of enzyme obtained from Cryptococcus neoformans (50 KDa) [32], A. vinelandii (52 KDa) [33], dog liver (52.5 KDa) [34], A. aculeatus (52 ± 1.1 KDa) [15], goat erythrocyte (52 KDa) [35]. However, the value is lower than as reported from Pseudomonas W6 [29], pig liver [20], turkey erythrocyte [36], coriander [24] and rainbow trout [37]. The result revealed that pigeon pea glucose-6-phosphate dehydrogenase is a homodimer with molecular weight of 113 KDa and subunit molecular weight approximately equals to 55 KDa.…”
Section: Molecular Weight Determinationcontrasting
confidence: 47%
“…than reported from microbial and animal sources [15] [35] [38]. The V max value was found to be greater than the value reported from coriander (0.038 U/ml) [24]. The V max value from other plant sources has not been reported.…”
Section: Effect Of Substrate and Coenzyme Concentrationcontrasting
confidence: 40%
See 3 more Smart Citations